Arka çapraz bağdan köken alan tenosinovyal dev hücreli tümör - Selçuk YAVUZ; Mert ÇİFTDEMİR; Ebru TAŞTEKİN; Nurettin TAŞTEKİN (Cukurova Medical Journal, 2017)
Arka çapraz bağdan köken alan tenosinovyal dev hücreli tümör